INSERÇÃO DAS NOVAS TECNOLOGIAS NO ENSINO E NAS DECISÕES JURÍDICAS: QUAL O ESPAÇO PARA AS HUMANIDADES? - Pessôa, Tatiane de Fátima da Silva (2021)
The importance of the humanistic training facing the new technologies insertion, increasingly present and applied in the teaching and legal decisions, demonstrate the relevance of dealing with them in this research. This way, it is intended to contribute to enlarge the understanding the knowledge frontiers, unifying the importance of the humanities in the teaching practices. Thus, thinking about changes in the spheres of legal education linked to the humanities is to reflect on the constant insertions and technological evolutions established with the society evolution. More than this, working for the development of a humanistic culture, facing the new technologies and the digital culture, as well as their consequences for the society. Therefore, the studied problem in this research involves the insertion of the new technologies both in teaching and in the legal decisions of the professional who will act in the judicial sphere, as well as in the legal decisions of the proposed solution for society. For the development of this research the methodology is the hermeneutic-dialectic method in which it will provide greater proximity to the problem, thus enabling the improvement of the proposed ideas by the authors who deal with topics related to technology, the society of information, teaching, legal education, humanities and hermeneutics. It starts with a conceptual interpretive reading of the following authors: Hans Jonas, Hans-Georg Gadamer, Paul Ricoeur and Manuel Castells. The research technique will be data analysis through indirect documentation. As results obtained in this research, it was noticed and cited numerous technological advances in the Brazilian Courts, providing greater speed to the daily life in the Judiciary. However, legal decisions/sentences are not being decided by algorithms so far in Brazil, they remain under human hands, this application being fearfully leveraged, given the dangers of this choice. It was found that the space for the humanities is limited in legal education in the initial part of the curriculum, which will certainly reflect on the performance of law practitioners in general.